Hubungan Kreativitas Mahasiswa Terhadap Hasil Belajar Mata Kuliah Seni Dekorasi Ruang Khusus Program Studi Pendidikan Tata Rias Universitas Negeri Jakarta - Dokel Satiawan Jaya; Eti Herawati; Dwi Atmanto (Departement of Mathematics Education, 2024)
Learning outcomes are a benchmark for the success of a learning activity. Good learning outcomes can make it easier for students to develop their potential in a particular field. This research aims to determine the relationship between student creativity and learning outcomes in room decoration arts specifically for the cosmetology education study program. This research was conducted on Class of 2022 cosmetology students who took a special room decoration arts course. The method used is a survey with a correlation approach and involves a population of 45 students who are taking a special room decoration art course in the even semester of 2024. The sampling technique is the total population and uses a questionnaire with a Likert Scale which was previously tested to calculate validity and reliability, for learning outcomes taken from the final grade of the special room decoration arts course. Data analysis methods use correlation coefficients, determinant coefficients, and simple linear regression. The results of this research show that creativity has a positive relationship with learning outcomes in special room decoration arts courses for cosmetology education students. The correlation value obtained was 0.874, t_count 11.778, significance value = 0.001<0.05, regression equation Y=12.982+0.816X, and determinant coefficient 76.3%. Thus, the higher the student's creativity, the higher the results achieved in learning the art of special room decoration.